2021
DOI: 10.1016/j.cnsns.2020.105584
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis in COVID-19 within-host model with immune response

Abstract: Highlights Mathematical model to represent viral dynamics in COVID-19 patients. Stability Analysis in COVID-19 Within-Host Model Bifurcation analysis suggests that the virus replicates fast to overcome T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 32 publications
0
41
0
1
Order By: Relevance
“…A large number of works use mathematical and computational tools to model the Human Immune System (HIS) using distinct techniques, such as ordinary differential equations (ODEs) ( Perelson, 1989 ; Baker et al, 1997 ; Chang et al, 2005 ; Vodovotz et al, 2006 ; Jarrett et al, 2015 ; Bonin et al, 2016 ), partial differential equations (PDEs) ( Pettet et al, 1996 ; Su et al, 2009 ; Flegg et al, 2012 ; Pigozzo et al, 2013 ; Quintela et al, 2014 ), stochastic methods ( Chao et al, 2004 ; Xavier et al, 2017 ), cellular automaton and agents ( Celada and Seiden, 1992 ; Morpurgo et al, 1995 ; Kohler et al, 2000 ; Bernaschi and Castiglione, 2001 ; Pappalardo et al, 2018 ). On the other hand, very few papers were published describing the dynamics of SARS-CoV-2 ( Almocera et al, 2020 ; Du and Yuan, 2020 ; Hernandez-Vargas and Velasco-Hernandez, 2020 ; Xavier et al, 2020 ), although some additional non-peer-reviewed papers can also be found on the internet. Three out four published works ( Almocera et al, 2020 ; Du and Yuan, 2020 ; Hernandez-Vargas and Velasco-Hernandez, 2020 ) are based on the target cell-limited model proposed by Perelson (2002) : a system of three ODEs to model target cells, infected cells, and viruses.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of works use mathematical and computational tools to model the Human Immune System (HIS) using distinct techniques, such as ordinary differential equations (ODEs) ( Perelson, 1989 ; Baker et al, 1997 ; Chang et al, 2005 ; Vodovotz et al, 2006 ; Jarrett et al, 2015 ; Bonin et al, 2016 ), partial differential equations (PDEs) ( Pettet et al, 1996 ; Su et al, 2009 ; Flegg et al, 2012 ; Pigozzo et al, 2013 ; Quintela et al, 2014 ), stochastic methods ( Chao et al, 2004 ; Xavier et al, 2017 ), cellular automaton and agents ( Celada and Seiden, 1992 ; Morpurgo et al, 1995 ; Kohler et al, 2000 ; Bernaschi and Castiglione, 2001 ; Pappalardo et al, 2018 ). On the other hand, very few papers were published describing the dynamics of SARS-CoV-2 ( Almocera et al, 2020 ; Du and Yuan, 2020 ; Hernandez-Vargas and Velasco-Hernandez, 2020 ; Xavier et al, 2020 ), although some additional non-peer-reviewed papers can also be found on the internet. Three out four published works ( Almocera et al, 2020 ; Du and Yuan, 2020 ; Hernandez-Vargas and Velasco-Hernandez, 2020 ) are based on the target cell-limited model proposed by Perelson (2002) : a system of three ODEs to model target cells, infected cells, and viruses.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, very few papers were published describing the dynamics of SARS-CoV-2 ( Almocera et al, 2020 ; Du and Yuan, 2020 ; Hernandez-Vargas and Velasco-Hernandez, 2020 ; Xavier et al, 2020 ), although some additional non-peer-reviewed papers can also be found on the internet. Three out four published works ( Almocera et al, 2020 ; Du and Yuan, 2020 ; Hernandez-Vargas and Velasco-Hernandez, 2020 ) are based on the target cell-limited model proposed by Perelson (2002) : a system of three ODEs to model target cells, infected cells, and viruses. In this work, we use a set of fifteen ODEs to model not only the virus but also immune cells, antibodies and cytokines.…”
Section: Related Workmentioning
confidence: 99%
“…Mathematical models are usually used to depict the propagation of a virus [6][7][8][9][10][11][12], and so many scholars have proposed a lot of mathematical models to study the spreading laws of the COVID-19 virus [13][14][15][16][17]. Although strengthening personal protection helps to resist the virus [18], it is still very important to understand the law of virus transmission.…”
Section: Introductionmentioning
confidence: 99%
“…En este sentido, entender más sobre la dinámica del SAR-CoV-2, así como mejorar la estimación de los parámetros de la infección viral, será determinante para actuar de mane-ra eficiente. El trabajo desarrollado por Hernández-Vargas y Velasco-Hernández puede servir para la evaluación de enfoques teóricos de control para adaptar nuevos fármacos contra COVID-19 (Hernandez-Vargas and Velasco-Hernandez, 2020;Almocera et al, 2021).…”
Section: A Manera De Introducciónunclassified